Systemic inflamation, systemic effects and comorbidities in chronic obstructive pulmonary disease - Suša, Romana; Lazić, Zorica; Čekerevac, Ivan (Medicinski časopis, 2018)
Chronic obstructive pulmonary disease (COPD) is known to be characterized by inflammation both in the stable phase of the disease and during exacerbation. It has been shown that certain inflammatory mediators have a high level in systemic circulation, indicating systemic inflammation in COPD. The first recognized systemic effect of COPD is a disorder of the state of nourishment. Certain diseases, including COPD, can lead to cachexia where patients lose muscle mass despite adequate caloric intake. Inflammation in COPD also has an effect on increased protein catabolism, which leads to a decrease in body weight. Increased activity of enyzms matrix metalloproteinases family (MMP) in patients with COPD can lead to lung tissue destruction and the development of osteoporosis. It is considered that the most important role in the association between COPD and CVD disease is systemic inflammation . Low level of inflammation in small airways in COPD and Atherosclerotic plaques, may be potential factor in the development of both pathological processes. Systemic manifestations of COPD include numerous endocrine disorders of the pituitary gland, thyroid gland, gonads, adrenal glands and pancreas. The mechanisms by which HOBP affects the endocrine function are not entirely clear, but are likely to include hypoxemia, hypercapnia, systemic inflammation, and the use of systemic glucocorticoids. Explanation for significant depressive disorder in more advanced stages in COPD can be expressive dyspnoea, decreased physical activity, worse exercise tolerance, frequent exacerbations and systemic inflamataion which can lead to further physical activity decrease, social isolation, fear, and depression.